Daidzein and Genistein Content in Tempeh Products from Several Local Soybean Varieties: Kandungan Daidzein dan Genistein Dalam Produk Tempe Dari Beberapa Varietas Kedelai Lokal (Glycine Max (L.) Merrill) - Uswatun, Siti; Fitriansyah, Sani Nurlaela; Herawati, Irma Erika (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2025)
Background: Tempeh is a widely consumed food due to its health benefits, affordability, and suitability for long-term consumption. The production process of tempeh from soybeans involves several stages, including soaking, dehulling, and inoculation with Rhizopus oligosporus yeast. Fermentation plays a key role in enhancing the nutritional quality of tempeh, particularly by increasing the levels of aglycone isoflavones. Tempeh contains three major types of aglycone isoflavones: daidzein, glycitein, and genistein. Among these, daidzein and genistein are classified as phytoestrogens due to their structural similarity to endogenous estrogen and their associated health-promoting properties. Objectives: This study was conducted on six different soybean seed varieties and their corresponding tempeh products, processed using traditional methods and subjected to three different fermentation durations (42, 47, and 52 hours). Methods: Soybean seeds and tempeh samples were extracted using a cold extraction method and analyzed for daidzein and genistein content through the standard addition method. Results: The results indicated variations in daidzein and genistein content across the six soybean varieties and among tempeh products fermented for different durations. The tempeh produced from the Dering 1 soybean variety showed the highest daidzein content (2.59%), while the Devon 1 variety exhibited the highest genistein content (2.13%) after 47 hours of fermentation. Conclusions: These findings support the potential of tempeh made from local soybean varieties as a functional food, due to their elevated levels of bioactive isoflavones.